O GURU DO ÓDIO: redes de poder e condução de conduta nos discursos de Olavo de Carvalho na plataforma Facebook (2015-2021) - Pullin, Lucas Monteiro (2023)
This research aims to analyze the speeches of the brazilian writer Olavo de Carvalho on the social networking platform Facebook. Through Michel Foucault's theoretical glasses, the work aims to understand some strategies used by Carvalho for the exercise of power and the conduct of his followers' conduct. Considered one of the main digital influencers of the conservative and far-right movements that gained strength in Brazil from 2013 onwards, Carvalho propagates lies, denialist ideas, conspiracy theories, hatred and resentment, supported by the characteristics of content transmission on digital platforms. Starting from the control switches of the speeches, an attempt is made to make a diagnosis of the present to arrive at the characteristics of biopower present in the lines of the Brazilian writer. Biopower, in this research, will be understood as formed by disciplinary, sexuality and security devices, in the terms proposed by Foucault, to better understand the normalization society which Olavo de Carvalho seems to seek. For this, the corpus of the research covers the years 2015 to 2021, a period in which important events for the recent history of Brazil occurred, such as the impeachment of former president Dilma Rousseff, the campaign for the presidency of Jair Bolsonaro, the beginning of the Bolsonaro’s government in the Presidency of the Republic and the Covid-19 pandemic. This period is also understood as the one through which there was a strengthening of conservative and far-right ideas within brazilian society, hence the importance of paying attention to Carvalho’s discourses. In the first chapter, this research is based on concepts of lie and truth in posts made during the pandemic. The period, which runs from the beginning of 2020 to the end of 2021, shows that Carvalho questions knowledge accepted by society, such as science, for example, based on denialist strategies to minimize the effects of the coronavirus and the effectiveness of vaccines. In the second chapter, the normalization society will be brought to the research to identify the notions of normal subject, the one who follows the moral rules of a society, of the abnormal, as the one who is deviant. Finally, in the third chapter, this work seeks to show how Carvalho will produce speeches to disqualify the press and universities to impose a regime of truth based on information and lies.